Intestinal Lipase Characterization in Common Snook (Centropomus undecimalis) Juveniles - Bartolo Concha-Frías; Martha Gabriela Gaxiola-Cortes; Fanny Janet De la Cruz-Alvarado; Luis Daniel Jimenez Martinez; Emyr Saul Peña-Marin; Marcia Angélica Oliva-Arriagada; Joe Luis Arias-Moscoso; Carlos Alfonso Alvarez-González (Fishes, 2022)
The common snook (Centropomus undecimalis) is a euryhaline fish with high commercial demand in the Mexican southeast, Caribbean, and South America. However, some aspects of its digestive physiology are still unknown, particularly in relation to lipid hydrolysis. Therefore, the characterization of the digestive lipase of this species was carried out. Our results show that the digestive lipase’s optimal temperature is 35 °C, being stable between 25 and 35 °C, and shows maximum activity at pH 9, with stability between pH 5 and 8. Different degrees of inhibition were presented by Orlistat (61.4%), Ebelactone A (90.36%), Ebelactone B (75.9%), SDS 1% (80.7%), SDS 0.1% (73.5%), and SDS at 0.01% (34.9%). Orlistat and Ebelactone A and B completely inhibited the lipase band in the zymogram, but not SDS addition. Lipase showed a molecular weight of 43.8 kDa. The high lipase activities in the digestive tract indicate the importance of lipids in the diet of C. undecimalis.